TAʿLĪM AL-LUĠAH AL-ʿARABIYYAH FĪ AL-MAʿĀHID AL-ISLĀMIYYAH FĪ INDŪNĪSIYYĀ - Noor Sa'adah (UIN ANTASARI, 2020)
This study aims to describe the academic material in Arabic teaching in the salaf and the modern Institutions, and describe the similarities and differences of Arabic teaching in both of them.The study used a qualitative. In this study the data were collected by using interviews, observation, and documentation. To analyze the data, the researcher used the interactive technique of Miles and Huberman, while to test the validity of the data, the method of triangulation technique was used.The result of the study shows the following: (1) The Arabic teaching materials in Rasyidiyah Khalidiyah Islamic boarding schools consist of 10 subjects, while in the Raudhatut Thalibin only consist of 5 subjects. The Rasyidiyah Khalidiyah boarding schools use theory of integrated and separated system in their Arabic teaching materials, while the Raudhatut Thalibin use separated system theory; (2) The instructional method engaged in Arabic teaching is the eclectic method. The teaching use concrete (indrawi) media. Both oral and written test were applied in the evaluation system; (3) The kinds of language environment applied in Arabic teaching in Rasyidiyah Kalidiyah Islamic boarding school consist of the environment of listening and reading. While speaking, reading and listening environments, were applied in Raudhatut Thalibin Islamic boarding school.Keywor